PSXVI-6 Diet deprivation followed by compensatory feeding of gestating gilts does not affect lactation performance. (7th December 2018) - Farmer, C; James, B; Herkelman, K; Lessard, P; Samson, A; Cormier, I
Abstract: The impact of diet deprivation followed by over-allowance during gestation on metabolic status of pregnant gilts and their lactation performance was determined. Gilts were fed a standard diet until d 27 of gestation and were subsequently reared under a control (CTL; n = 28) or an experimental (TRT; n = 26) dietary regimen. The experimental regimen provided 70% (restriction diet, RES) and 115% (over-allowance diet, OVER) of the CP and NE content provided by the CTL diet. The RES diet was given to TRT gilts, from d 28 to 74 of gestation followed by the OVER diet from d 75 until farrowing. All gilts were fed 2.5 kg of feed daily. Piglets were weighed weekly until weaning (d 21) and milk samples were collected on d 19 of lactation. Blood samples were obtained on d 28, 75 and 110 of gestation, and on d 3 and 20 of lactation to measure concentrations of IGF-I, urea, FFA and glucose. The MIXED procedure of SAS with treatment as the main effect was used for statistical analyses. The TRT gilts gained less BW than CTL gilts (17.3 vs 31.7 kg; P < 0.01) from d 28 to 75 of gestation and gained more BW (29.5 vs 21.9 kg; P < 0.01) from d 75 to 110, but their overall gain from mating to d 110 was lower (61.4 vs 67.2 kg; P < 0.05). Metabolic status during gestation was affected, with TRT gilts having less IGF-1 and urea, and more FFA than CTL gilts on d 75 (P < 0.01), and more urea on d 110 (P < 0.01). Neither growth of suckling piglets nor milk composition in late lactation was affected by treatment. In conclusion, diet deprivation and subsequent compensatory feeding of gestating gilts did not improve lactation performance.